(7x+3) x (4x-5)
7x*4x = 28x^2
7x*-5 = -35x
3+4x = 12x
3*-5 = -15
so you get 28x^2 -23x -15
Answer: The required multiplied expression is [tex]28x^2-23x-15.[/tex]
Step-by-step explanation: We are given to multiply the following linear factors and write the answer is standard form :
[tex]M=(7x+3)(4x-5)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We will be using the following distributive property :
[tex](a+b)(c+d)=a(c+d)+b(c+d).[/tex]
From (i), we get
[tex]M\\\\=(7x+3)(4x-5)\\\\=7x(4x-5)+3(4x-5)\\\\=28x^2-35x+12x-15\\\\=28x^2-23x-15.[/tex]
Thus, the required multiplied expression is [tex]28x^2-23x-15.[/tex]